PENGGUNAAN MEDIA SOSIAL INSTAGRAM DALAM MEMBENTUK CITRA DIRI REMAJA PADA SANTY SASTRA PUBLIC SPEAKING - Puspadewi, I Dewa Ayu; Siswadi, Gede Agus (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
The progress of the times is marked by technological sophistication. As proof of technological sophistication is the presence of social media that makes it easy and comfortable. One of the popular social media used by prioritizing visual content is Instagram. The use of Instagram social media for Santy Sastra Public Speaking teenagers is an interesting thing to research because teenagers actively display the self-image they want through Instagram social media. This study focuses on discussing the advantages of Instagram social media, strategies, and the effects of Instagram social media in shaping adolescent self-image in Santy Sastra Public Speaking. The theories used in this research are: 1) Uses and Gratification Theory, 2) Agenda Setting Theory, and 3) The Dependency Theory of Mass Communication Effects. This study uses a qualitative research method with a descriptive approach. Collecting data in this study through observation, interviews, questionnaires and literature study. The results of this study indicate 1) Instagram social media is massive and popular, Instagram social media has complete features that can meet the needs of teenagers in forming their self-image as public speakers, 2) the strategies used include consistency of appearance on Instagram social media, selective in uploading, and prioritizing content. 3) the effect of using Instagram social media in shaping adolescent self-image in Santy Sastra Public Speaking, including cognitive effects in the form of expanding confidence in self-image and strengthening personal identity, affective effects in the form of giving a positive impression and releasing tension, behavioral effects in the form of being wise in displaying content and temporarily close the account if it affects emotionally.